Hubungan Antara Konsumsi Tablet Fe Dan Frekuensi Antenatal Care (Anc) Dengan Kadar Hemoglobin Pada Ibu Hamil Di Desa Sendang Ponorogo - Khristyka, Ninda; , Dwi Sarbini, SST, M.Kes; , Endang Nur W, S.St., M.Si.Med (2014)
Introduction . Anemia is the condition with blood hemoglobin level of less than 12 g%, while anemia in pregnancy is the maternal condition with hemoglobin level below 11 g% in the first and second trimester or level of <10.5 g% in the second trimester. Considering the survey in January 2014 in Puskesmas Sendang Ponorogo, there was 42% pregnant women visit, while data of anemia in this area showed high level of 67.58%. The proportion of pregnant women having their hemoglobin level examined during pregnancy was 55.8%. Objective . This research aimed to find out the relationship of Fe and Antenatal Care Frequency (ANC) to Hb level in pregnant women. Method. The type of research used was an observational research using cross sectional approach and sampling technique used was simple random sampling. The Hb level value obtained from Hb examination using Cyanmethemoglobin, data of Fe table consumption and ANC frequency were obtained from questionnaire. The data analysis was carried out using Pearson's product moment correlation. Result. The Fe tablet consumption was less than 63.3%, ANC frequency less than 66.7%, anemic Hb level 53.3%. The result of correlation test on Fe tablet consumption and Hb level obtained p value < 0.05. The result of test on ANC frequency and Hb level obtained p value < 0.05. Conclusion. There was a relationship between Fe tablet consumption and Hb level. There was a relationship between ANC frequency and Hb level. Recommendation. Further studies should be conducted on the relationship of Fe tablet consumption and ANC frequency to Hb level, to improve the anemic state in pregnant women.